Pengaruh Jiwa Kewirausahaan dan Manajemen Agribisnis terhadap Keberhasilan Gapoktan Simantri di Kabupaten Tabanan - Dananjaya, IGAN.; Suparta, N.; Setiawan AP, I G. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Bali Provincial Government has been implementing a program Simantri since 2009, until now reached the number of 419 units Simantri. Simantri program is a groundbreaking effort to further streamline farm through crop and livestock waste utilization with concept of no waste (zero waste). Simantri success is influenced by many factors, among others the ability of entrepreneurship and agribusiness management.The purpose of this study was to analyze the effect of entrepreneurship and agribusiness management towards the successful of Simantri in Tabanan. The study was conducted on Gapoktan Simantri from 2009-2011. The unit of analysis is the study Poktan Simantri executor. The number of samples was determined by 21 Poktan executive with 84 respondents consisting of administrators and members representing. Engineering analysis data using Partial Least Square (PLS) with the help of Smart PLS program . The results showed that the entrepreneurial spirit is very significant positive effect on the success of Simantri, as well as the management of agribusiness. Agribusiness management turns a very significant positive effect on the success of Simantri. This suggests that the entrepreneurial spirit of great influence in shaping the quality of human resources so as to implement agribusiness management and eager to achieve the performance in implementing Simantri. Suggestions for implementing Poktan of Simantri members is that the entrepreneurial spirit should grow or strengthened, especially in changing the mindset of associating with a more flexible search for information to Simantri who has managed to be more motivated to be successful running the Simantri. Poktan Simantri implementing institutional groups should also increasing so as to innovate in developing technology based agribusiness innovation with the development of diversified products in Simantri.
Keywords: Simantri, the Spirit of Entrepreneurship, Agribusiness Management, and Success